Development and Research of Cephalosporin Antibiotics - Wu, Yutong (International Journal of Public Health and Medical Research, 2025)
Cephalosporins are a class of broad-spectrum antibiotics. Due to their broad spectrum, high efficacy, strong antibacterial activity, and minimal side effects, they have gained significant clinical attention. With the increase in bacterial infections and the widespread use of cephalosporins, there has been an increase in bacterial resistance to cephalosporin drugs and an increase in adverse reactions. The development of new cephalosporin drugs has become a major direction. This study reviews the changes in cephalosporin synthesis routes and the historical development of cephalosporin drugs, and discusses the challenges and progress in antibiotic drug research. It aims to provide insights for developing new cephalosporin drugs that are more effective against resistant bacteria and have stronger activity.